Perburuan Harimau di Bali pada Awal Abad XX Berdasarkan Sumber-Sumber Kolonial - Hikmana Arafah Wiryandara; Dimas Nugroho; Harriyadi (PURBAWIDYA: Jurnal Penelitian dan Pengembangan Arkeologi, 2024)
Before falling into the hands of the Dutch colonial government in the early 20th century, Bali was quite a foreign and restricted territory for Europeans. This condition slowly changed when the colonial government conquered the local Balinese kingdoms. Tigers' existence in Bali was later known through the records created by Europeans who studied nature and the local community there. This study aims to show the link between the conquest of Bali by the colonial government and the extinction of the Bali tiger. Through historical research methods to examine the literature sources used, this study shows that the expansion of colonial government influence in Bali also played a role in the process of extinction of the Bali tiger. The growth of private plantations in areas home to tigers further increases the potential for conflict between tigers and humans. Similar to Javan and Sumatran tigers, Bali tigers are also often hunted because they disturb and threaten plantation activities, as well as because they are a prey object for sport-hunting enthusiasts. Extinction is inevitable as a consequence of continuous hunting activities for this species.